2017
DOI: 10.1007/s12298-017-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria brassicae interactions with the model Brassicaceae member Arabidopsis thaliana closely resembles those with Mustard (Brassica juncea)

Abstract: Alternaria leaf blight, a disease of oilseed Brassicas is caused by a necrotrophic phytopathogenic fungus . The details of its pathogenesis and defence responses elicited in the host upon infection have not been thoroughly investigated. Here, accession Gre-0 was identified to be highly susceptible to . A comparative histopathological analysis for disease progression and plant responses to in and revealed significant similarities between the two compatible pathosystems. Interestingly, in both the compatible hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Following germination, A. brassicae invades the host tissue by developing Appressoria Like swollen, globular Structures (ALS) at the hyphal apices. Similar Appressoria like structures were also observed when the fungus invaded its natural host B. juncea (Mandal et al, 2018). Fungal penetration attempts could be observed in all accessions ( Supplementary Table S2).…”
Section: Comparable Spore Germination and Penetration On Resistant Ansupporting
confidence: 71%
See 3 more Smart Citations
“…Following germination, A. brassicae invades the host tissue by developing Appressoria Like swollen, globular Structures (ALS) at the hyphal apices. Similar Appressoria like structures were also observed when the fungus invaded its natural host B. juncea (Mandal et al, 2018). Fungal penetration attempts could be observed in all accessions ( Supplementary Table S2).…”
Section: Comparable Spore Germination and Penetration On Resistant Ansupporting
confidence: 71%
“…Also, it is well established that ABA induces closure of stomata. Stomata have been shown to be the major penetration site of A. brassicae in our previous study (Mandal et al, 2018). Therefore, ABA might have an important role in defence against A. brassicae.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The GORK mutant has been reported to show limited stomatal closure in response to abscisic acid (ABA) and jasmonic acid (JA) (Becker et al, 2003). A previous study in Brassica juncea (Giri et al, 2013) and studies from our laboratory (Mandal et al, 2017) have shown that A. brassicae preferentially penetrates through stomatal openings. The culture filtrate of A. brassicae caused infection-like symptoms on both resistant and susceptible accessions and mimicked the spore inoculation symptoms very closely.…”
Section: Novel Genes Influencing Disease Resistance To a Brassicaementioning
confidence: 89%